Immune markers and human leukocyte antigen polymorphisms associated with disease severity in systemic lupus erythematosus - Selvaraja, Malarvili (2019)
Systemic Lupus Erythematosus (SLE) is characterized as the prototypic systemic autoimmune disease affecting multiple organs. It typically affects females at far greater rates than males with a ratio of 9:1. SLE is a heterogeneous disease and patients may present with malar and discoid rash, photosensitivity, clinical ulcers, arthritis, renal, neurological, hematological and immunological disorders. Lupus nephritis affects about 25-70% of SLE patients, and is one of the more serious manifestations as it can lead to complete renal failure. Despite decades of research efforts, the pathogenesis of SLE and mechanism of organ damage among SLE patients not fully understood. This study hypothesize variation in MHC class I and class II genes polymorphism, cytokines, free radicals and T helper cells expression may influence disease severity and organ involvement in SLE patients. Thus, the present study was aimed to investigate immunologic factors that influence clinical parameters and disease severity and lab parameters in SLE. Total of 100 SLE patients with and without lupus nephritis (LN) were recruited from Hospital Serdang, Serdang, Selangor Malaysia from the period of January to October 2016. Twenty-five (25) heathy volunteers were recruited as comparison group for cytokine and free radical analysis. The comparison for HLA genotyping, published data containing 951 data were used. HLA genotyping conducted using PCR-SSO (Lifecodes, R&D Systems, Germany). Cytokines and free radical’s levels from plasma were detected using ELISA and multiplex whereas T helper subsets (Th1, Th2, Th9/Th17/Th22, Tregs, TCR-) were detected with multicolor flow cytometry. Results obtained from genotyping of HLAclass I alleles showed an appreciable increase in allele frequencies with increased risk for HLA-B*3802. Whereas, for HLA class II, several alleles including HLADRB1* 0405, -*1201, -*1502, -*1602, HLA-DQB1*0301, -*0501, -*0502 alleles showed increased risk while HLA-DRB1*1201 and HLA-DQB1*0301 alleles showed protective role in SLE. HLA-DRB1*04 showed significant association to lupus nephritis and arthritis while HLA-DRB1*15 with oral ulcer. HLA-DQB1*05 significantly associated to SLAM (Systemic Lupus Activity Measure) and SLEDAI (Systemic Lupus Erythematosus Disease Activity Index) score and HLA-DRB1*04 to CRP. Several alleles found to be significantly associated to cytokines, T helper cells and free radicals including HLA-B*38 with Th1 and Th2, HLA-A*11 with TNF-α, HLA-DRB1*04 with cytokines (VEGF, IL-18, IL-21, IL-17F, IL-7, IL-5, IFN-y, GMCSF) and free radicals (LPO and catalase). HLA-DRB1*15 were significantly associated with IL-2 and IL-10. For cytokine expressions, IFN-y, TNF-α, IL-10, IL-9, IL-13, IL-17F, IL-25, IL-35, IL-21, IL-8 showed significantly (P<0.001) elevated level as well as cytokines GM-CSF, IL-6, IL-18, IL-15 and VEGF (P<0.01) in SLE patients as compared to control group. IL-2 and IL-5 were significantly (P<0.001) inhibited in SLE patients as compared to control group. For T helper subset, only Tregs showed significant (P<0.001) inhibition in SLE patients compared to control group. Free radical’s analysis showed catalase, superoxide dismutase and glutathione peroxidase were significantly (P<0.001) inhibited and lipid peroxidation were increased in all SLE patients as compared to control group. Several cytokines such as TNF-α, IL-5, IL-10, IL-2 and free radical catalase were significantly correlated with SLAM and SLEDAI score. For clinical parameter only C4 was correlated to SLEDAI score whereas ESR, hemoglobin, platelet, WBC, neutrophil, monocytes, eosinophil, total protein and creatinine were significantly associated to both SLAM and SLEDAI index. As conclusion, this study was able to identify several potential mechanisms for induction of severe disease symptoms. These may be useful as markers to identify patients with severe symptoms such as lupus nephritis and potential targets for alternative therapy.